Direct comparison of rapid deployment versus sutureless aortic valve replacement: a meta-analysis - Sohn, Suk Ho (J Thorac Dis, 2021)
BACKGROUND: This meta-analysis was conducted to compare the procedural and early outcomes of aortic valve replacement (AVR) using rapid deployment valve (RD group) versus sutureless valve (SU group). METHODS: A literature search of 5 online databases was conducted. The primary outcomes were mean transvalvular pressure gradient (MPG) after AVR, the incidence of paravalvular leak (PVL) and the need for a permanent pacemaker implantation (PPI). The secondary outcomes included aortic cross-clamp (ACC) and cardiopulmonary bypass (CPB) times, early mortality and other postoperative complications, such as atrial fibrillation, bleeding reoperation and stroke. RESULTS: Eight articles were included, and all outcomes except MPG after AVR in matched valve sizes were extracted from 7 studies (RD group =842 patients and SU group =1,386 patients). The pooled analysis demonstrated a lower MPG in the RD group than in the SU group, with mean difference (MD) of 2.64 mmHg. The pooled risk ratios of any PVL and grade ≥2 (or moderate) PVL were not significantly different between the groups; however, the incidence of PPI was significantly lower in the RD group than in the SU group, with a risk ratio of 0.69. The pooled analyses showed that the ACC and CPB times were significantly longer in the RD group than in the SU group, with weighted MDs of 8.74 (P<0.001) and 9.94 (P<0.001) minutes, respectively. The risks of early mortality and other postoperative complications were not significantly different between the groups. CONCLUSIONS: AVR using RD valve was associated with better valve hemodynamics in terms of the MPG than AVR using SU valve, and better outcomes were observed in the RD group regarding PPI. Procedural times were longer in AVR using RD valve than SU valve. Early clinical outcomes showed no difference between RD and SU valve.